Sampling - Thompson, Steven K., 1945- (Hoboken, N.J. : Wiley, 2012)
"The Third Edition retains the general organization of the prior two editions, but it incorporates new material throughout the text. The book is organized into six parts: Part I covers basic sampling from simple random sampling to unequal probability sampling; Part II treats the use of auxiliary data with ratio and regression estimation and looks at the ideas of sufficient data, model, and design in practical sampling; Part III covers major useful designs such as stratified, cluster and systematic, multistage, and double and network sampling; Part IV examines detectability methods for elusive populations, and basic problems in detectability, visibility, and catchability are discussed; Part V concerns spatial sampling with the prediction methods of geostatistics, considerations of efficient spatial designs, and comparisons of different observational methods including plot shapes and detection aspects; and Part VI introduces adaptive sampling designs in which the sampling procedure depends on what is observed during the survey. For this new edition, the author has focused on thoroughly updating the book with a special emphasis on the first 14 chapters since these topics are invariably covered in basic sampling courses. The author has also implemented new approaches to explain the various techniques in the book, and as a result, new examples and explanations have been added throughout. In an effort to improve the presentation and visualization of the book, new figures as well as replacement figures for previously existing figures have been added. This book has continuously stood out from other sampling texts since the figures evoke the idea of each sampling design. The new figures will help readers to better visualize and understand the underlying concepts such as the different sampling strategies"--
Machine generated contents note: Preface to the Third EditionPreface to the Second Edition xiiiPreface to the First Edition xv1. Introduction 1Part I. Basic Sampling 92. Simple Random Sampling 113. Confidence Intervals 294. Sample Size 355. Estimating Proportions, Ratios, and Subpopulation Means 396. Unequal Probability Sampling 51Part II. Making the Best Use of Survey Data 657. Auxiliary Data and Ratio Estimation 678. Regression Estimation 899. The Sufficient Statistic in Sampling 10110. Design and Model 107Part III. Some Useful Designs 11511. Stratified Sampling 11712. Cluster and Systematic Sampling 12913. Multistage Designs 14314. Double or Two-Phase Sampling 157Part IV. Methods for Elusive and Hard-to-Detect Populations 17115. Network Sampling and Link-Tracing Designs 17316. Detectability and Sampling 18517. Line and Point Transects 19918. Capture-Recapture Sampling 23319. Line-Intercept Sampling 245Part V. Spatial Sampling 25520. Spatial Prediction or Kriging 25721. Spatial Designs 27122. Plot Shapes and Observational Methods 275Part VI. Adaptive Sampling 28323. Adaptive Sampling Designs 28524. Adaptive Cluster Sampling 28925. Systematic and Strip Adaptive Cluster Sampling 30926. Stratified Adaptive Cluster Sampling 323Answers to Selected Exercises 339References 343Author Index 361Subject Index 365.
Includes bibliographical references and indexes.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Sampling (Statistics); Electronic books